Participatory Approaches in the Formulation of Public Policy at Nagari Governance Level - Akmal, Artha Dini; Nurhabibi, Pratiwi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2021)
The smallest administrative unit in West Sumatra is not known as the village government but the Nagari government. West Sumatra uses the name Nagari Government to respond to the implementation of regional autonomy, which gives local governments the freedom to manage their government according to their respective local wisdom. It has the same main tasks and functions. In terms of public policymaking (policy formulation), there is still an element of adat in the policy formulation process. West Sumatra involved several actors in making this Nagari regulation, including Walinagari and its apparatus, BPRN (Nagari People's Representative Body), and KAN (Nagari Customary Density). What often happens is that many Nagari governments issue Nagari regulations based on routine activities. In contrast, regulations that are derived from people's aspirations can be said to have not existed in the 2017-2019 period. As happened in 6 Nagari in the salimpaung sub-district, there is no Nagari regulation made based on the community's needs. So far, the Nagari regulations are made to meet the needs of routine activities such as the preparation of the Nagari budget and development plans. This phenomenon has attracted the attention of researchers because the Nagari government also has the responsibility to make rules according to the needs of the community. The researcher also wants to know how the community participates in the process of formulating Nagari regulations, can these Nagari regulations be by the people's choices